1991
DOI: 10.1007/bf01709877
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamines and oxygen consumption during weaning from mechanical ventilation

Abstract: Previous studies on oxygen consumption (VO2) during weaning from mechanical ventilation assumed that an increase in VO2 (delta VO2) reflected oxygen consumption by respiratory muscles (VO2RESP), and proposed delta VO2 as a weaning predictor. We measured VO2 CO2 production (VCO2) and plasma catecholamines in 20 short-term ventilated patients during weaning by SIMV and CPAP. delta VO2 as a percentage of VO2 during spontaneous ventilation (delta VO2%) ranged from 4.8% to 41.5%. VCO2 also increased and correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 20 publications
4
21
0
4
Order By: Relevance
“…This hypothesis was also supported by nirV9O 2 evolution, an estimation of local oxygen consumption that corrects DeO 2 for the local haemoglobin content [20]. This finding might reflect increased sympathetic outflow trying to compensate for the inadequate cardiovascular response, as supported by other studies that showed a significant increase in plasma catecholamine levels during WT, especially in failure to wean patients [28][29][30].…”
Section: Discussionsupporting
confidence: 54%
“…This hypothesis was also supported by nirV9O 2 evolution, an estimation of local oxygen consumption that corrects DeO 2 for the local haemoglobin content [20]. This finding might reflect increased sympathetic outflow trying to compensate for the inadequate cardiovascular response, as supported by other studies that showed a significant increase in plasma catecholamine levels during WT, especially in failure to wean patients [28][29][30].…”
Section: Discussionsupporting
confidence: 54%
“…However, the higher fC and lower SBP noted in these patients are probably associated with an increase in catecholamine release. Increased sympathetic activity during weaning has been related [5,19,23,24] to plasma noradrenaline levels significantly higher in patients in whom weaning failed [23]. In the current study, this assumption is supported by the apparently enhanced fC and SBP in patients with weaning failure.…”
Section: Discussionsupporting
confidence: 75%
“…The mean plasma norepinephrine levels significantly increased from 1.13 ± 0.55 ng/ml on CMV to 1.85 ± 0.96 ng/ml during spontaneous breathing, and epinephrine levels significantly increased from 0.10 ± 0.05 to 0.20 ± 0.13 ng/ml, respectively. Similarly, in another study by Oh and coworkers 21 , increases in plasma catecholamine levels during weaning trials were found. Mean plasma epinephrine levels significantly increased from 136 pg/ml on CMV to 508 pg/ml during weaning, and norepinephrine levels increased from 483 to 1143 pg/ml, respectively.…”
supporting
confidence: 55%